2011
DOI: 10.1103/physrevlett.106.016803
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Coulomb Blockade and Zero Bias Anomaly in a Strongly Coupled Nanodot

Abstract: The current-voltage characteristics through a metallic nanoparticle which is well coupled to a metallic lead are measured. It is shown that the I-V curves are composed of two contributions. One is a suppression of the tunneling conductivity at the Fermi level, and the second is an oscillating feature which shifts with gate voltage. The results indicate that zero-bias anomaly and Coulomb blockade phenomena coexist in an asymmetric strongly coupled zero-dimensional system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…[8,9]. Experiments employing quantum dot thermometry [10,11,12,13], investigating electrical conduction in metallic nanodots [14] or granular films [15] work in this intermediate Coulomb blockade regime as well.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[8,9]. Experiments employing quantum dot thermometry [10,11,12,13], investigating electrical conduction in metallic nanodots [14] or granular films [15] work in this intermediate Coulomb blockade regime as well.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We note that although items (i), (ii) and (iv) are in qualitative agreement with our theory, observations (iii) and (v) are formally at odds with the observations of Refs. [26,21]. We note that feature (iii) can be related with the fact that the total tunneling conductance is not large enough (g ∼ 3) such that application of our theory is questionable.…”
Section: Final Resultsmentioning
confidence: 97%
“…In recent experiments [26,21] the electron transport via highly asymmetric SET at low temperatures was studied. For several samples with 1 < g < 10 distinct…”
Section: Final Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely explanation for the gap observed in our experiment is that it arises from effect of exchangetype zero-bias anomaly (ZBA) on single electron tunnelling of Au NPs. Very recently, Bitton, et al reported that in the region, k B T<< e 2 /C and R t ~ R q , the effects of ZBA and CB would coexist in an isolated Au NP [24].…”
mentioning
confidence: 99%